2016
DOI: 10.1002/1878-0261.12012
|View full text |Cite
|
Sign up to set email alerts
|

Multiregion ultra‐deep sequencing reveals early intermixing and variable levels of intratumoral heterogeneity in colorectal cancer

Abstract: Intratumor heterogeneity (ITH) contributes to cancer progression and chemoresistance. We sought to comprehensively describe ITH of somatic mutations, copy number, and transcriptomic alterations involving clinically and biologically relevant gene pathways in colorectal cancer (CRC). We performed multiregion, high‐depth (384× on average) sequencing of 799 cancer‐associated genes in 24 spatially separated primary tumor and nonmalignant tissues from four treatment‐naïve CRC patients. We then used ultra‐deep sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
46
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 49 publications
6
46
0
Order By: Relevance
“…As already noted above, it has been shown that, at least in CRC, there is about 80% concordance between somatic mutations found in primary and metastatic tumours1011. Also, recent studies by us – using targeted capture sequencing with the same 799-gene panel used here – as well as others, have further demonstrated that there is a high level of concordance of mutations present across different sectors of patients’ primary colorectal tumours212223. As such, tumour heterogeneity should not significantly affect our assays.…”
Section: Discussionsupporting
confidence: 73%
“…As already noted above, it has been shown that, at least in CRC, there is about 80% concordance between somatic mutations found in primary and metastatic tumours1011. Also, recent studies by us – using targeted capture sequencing with the same 799-gene panel used here – as well as others, have further demonstrated that there is a high level of concordance of mutations present across different sectors of patients’ primary colorectal tumours212223. As such, tumour heterogeneity should not significantly affect our assays.…”
Section: Discussionsupporting
confidence: 73%
“…Computational modeling of spatial tumor growth and statistical inference on the genomic data revealed that most detectable ITH occurs early during tumor growth, long before the lesion is clinically evident. These findings were subsequently corroborated by reports that subclonal alterations originate early in colorectal adenomas/carcinomas [4548]. Hence, ITH is already present in early lesions and continues to accrue during progression.…”
Section: Genetic and Non-genetic Tumor Heterogeneitysupporting
confidence: 78%
“…Subsequent studies have corroborated aspects of ‘Big Bang’ dynamics [46, 47, 247], suggesting that they may be relatively common in colorectal tumors. Others have considered more strict models of neutrality.…”
Section: Evolutionary Forces Determining the Extent Of Genetic Hetmentioning
confidence: 90%
“…A primary goal of modern cancer research is to characterize this evolutionary process, so as to enable precise, patient-specific prognostic forecasts and to optimize targeted therapy regimens.Much progress has been made in revealing the evolutionary features of particular cancers, yet these findings raise as many questions as they answer. Why do different tumour types exhibit different modes of evolution [1,3,4,5,6]? What conditions sustain the frequently observed pattern of branching evolution, in which several clones diverge and evolve in parallel [1,7]?…”
mentioning
confidence: 99%